CLINICAL STUDY ON FETAL OUTCOMES OF JAUNDICE DURING PREGNANCY IN AT MADHUBANI MEDICAL COLLEGE. - kumari, Nilu (Student’s Journal of Health Research Africa, 2024)
Background Jaundice during pregnancy, arising from various etiologies, poses significant risks to mother and fetus health, containing preterm birth, intrauterine growth restriction, and fetal demise. The study aims to investigate the fetal outcomes of pregnant women presenting with jaundice or deranged liver function tests. Methods A prospective observational study involving 40 pregnant women with jaundice or abnormal liver function tests was conducted. Demographic, clinical, laboratory, and imaging data were collected, and patients were monitored through the antepartum, intrapartum, and postpartum periods. Outcomes assessed included gestational age at delivery, mode of delivery, and both fetal and maternal outcomes. Statistical analysis was used to identify significant associations. Results The mean age was 28.5 years, with a mean gestational age at presentation of 30.2 weeks. Common symptoms were jaundice, vomiting, pruritus, and dark urine. Elevated liver enzymes were noted in all patients. Fetal outcomes included 80% term deliveries, 87.5% live births, 7.5% intrauterine fetal demise, 5% stillbirths, 22.5% NICU admissions, and 5% early neonatal deaths. Maternal outcomes included fulminant liver failure (10%), disseminated intravascular coagulation (5%), eclampsia (5%), 12.5% ICU monitoring, and 2.5% maternal mortality. Significant associations were found between severe jaundice and preterm deliveries, abnormal liver function tests and NICU admissions, and a history of hepatic failure with adverse maternal outcomes. Conclusion Jaundice during pregnancy notably impacts both mother and foetus outcomes, leading to increased risks of preterm delivery, neonatal intensive care unit admissions, and severe maternal complications. Early detection, vigilant monitoring, and comprehensive management are crucial to mitigate adverse outcomes. Recommendations Healthcare providers should adopt a multidisciplinary approach to managing jaundice in pregnancy, ensuring timely interventions and close monitoring to improve mother and fetus health outcomes. Further research is needed to develop standardized protocols for managing this condition.